(untitled) - Haber, Stephen H. (Cambridge, 2003)
This detailed economic history of Mexico presents a theory about how rent seeking permits economic growth and explains why political instability is not necessarily correlated with economic stagnation. It is intended for historians of Latin America, scholars interested in economic development, and political scientists interested in the political foundations of growth.
Keywords: Right of property,Quyền sở hữu; History,Lịch sử; Mexico,Mexico